2016
DOI: 10.1007/s00384-016-2661-z
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal tract anastomoses with the biofragmentable anastomosis ring: is it still a valid technique for bowel anastomosis? Analysis of 203 cases and review of the literature

Abstract: PurposeBiofragmentable anastomosis ring (BAR) is an alternative to manual and stapled anastomoses performed within the upper and lower gastrointestinal (GI) tract. The aim of this study was to evaluate the effectiveness of BAR utility for bowel anastomoses based on our own material.MethodsA retrospective analysis was performed to a total of 203 patients who underwent bowel surgery with the use of BAR anastomosis within upper and lower gastrointestinal tract between 2004 and 2014. Data for the analysis was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Furthermore, it has been shown that compression anastomoses can potentially be compared with conventional and staple suturing techniques in terms of safety and surgical outcome, or in some cases even produce better results. 32 , 35 , 36 , 38 , 77 , 86 , 95 , 96 Especially, the expulsion of the compression implants enabling a foreign-body-free healing process, leading to less scarring, deserves notice. In their meta-analysis, however, Slesser et al concluded that there were no advantages with regard to postoperative complications in favor of compression anastomoses 15 and our meta-analysis also did not provide any evidence of superiority.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that compression anastomoses can potentially be compared with conventional and staple suturing techniques in terms of safety and surgical outcome, or in some cases even produce better results. 32 , 35 , 36 , 38 , 77 , 86 , 95 , 96 Especially, the expulsion of the compression implants enabling a foreign-body-free healing process, leading to less scarring, deserves notice. In their meta-analysis, however, Slesser et al concluded that there were no advantages with regard to postoperative complications in favor of compression anastomoses 15 and our meta-analysis also did not provide any evidence of superiority.…”
Section: Discussionmentioning
confidence: 99%
“…Automatic devices for providing uniform anastomosis by reducing operator dependence are continuously being studied to reduce the anastomotic complications. Representatively, methods using a magnet such as Magnamosis or using a bio fragment ring (BAR) can avoid the user's deviation from the compression pressure 15,16 . However, in cases of Magnamosis using magnets or the BAR, it is difficult to adjust the compression force depending on the tissue condition and expected recovery characteristics; moreover, it is impossible to use such approaches in the low rectum 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Representatively, methods using a magnet such as Magnamosis or using a bio fragment ring (BAR) can avoid the user's deviation from the compression pressure. 15 , 16 However, in cases of Magnamosis using magnets or the BAR, it is difficult to adjust the compression force depending on the tissue condition and expected recovery characteristics; moreover, it is impossible to use such approaches in the low rectum. 17 Heretofore, circular staplers were usually applied for colorectal surgery and that was based on the operator's dependent manual compression.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is still an attractive alternative to other types of bowel anastomoses even a persistent intestinal obstruction risk. 34 We advocate practicing with fragmented rings before surgery to avoid this risk. This practice strategy has been used with Anastocom, and it should reduce the rate of postoperative obstruction due to nonexpulsion.…”
Section: Discussionmentioning
confidence: 99%